2021
DOI: 10.1177/00220345211029277
|View full text |Cite
|
Sign up to set email alerts
|

Social Mobility and Tooth Loss: A Systematic Review and Meta-analysis

Abstract: This study systematically reviews the evidence of the association between life course social mobility and tooth loss among middle-aged and older people. PubMed, Scopus, Embase, and Web of Science were systematically searched in addition to gray literature and contact with the authors. Data on tooth loss were collated for a 4-category social mobility variable (persistently high, upward or downward mobility, and persistently low) for studies with data on socioeconomic status (SES) before age 12 y and after age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
2
10
0
2
Order By: Relevance
“…Another cross-sectional study did not find an association between SES and dental caries in 18-year-old adolescents [ 19 ]. A recent meta-analysis found SES in childhood and adulthood to be associated with tooth loss, but concluded that “contextual factors” have to be considered when explaining the effects [ 38 ]. This means that personal factors such as genetics and SES cannot fully explain dental health or disease without considering environmental factors (e.g., social environment, food availability) and resulting (health) behaviors as mediators (e.g., hygiene and nutrition, health awareness and health care utilization).…”
Section: Discussionmentioning
confidence: 99%
“…Another cross-sectional study did not find an association between SES and dental caries in 18-year-old adolescents [ 19 ]. A recent meta-analysis found SES in childhood and adulthood to be associated with tooth loss, but concluded that “contextual factors” have to be considered when explaining the effects [ 38 ]. This means that personal factors such as genetics and SES cannot fully explain dental health or disease without considering environmental factors (e.g., social environment, food availability) and resulting (health) behaviors as mediators (e.g., hygiene and nutrition, health awareness and health care utilization).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the influence of upward mobility and stable low social mobility on oral health during adulthood [8][9][10]. A recent systematic review on the influence of social mobility on tooth loss concluded that individuals in the upwardly mobile, downwardly mobile, and persistently low socioeconomic group were more likely to have tooth loss than those with persistent high social status [3]. Existing dental literature has also shown the relationship between income decrease over three years follow-up and poor SROH as well as the association of downward and stable low social mobility with number of teeth during adulthood [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Oral health disparities refer to the social patterning of health resulted from the uneven distribution of diseases across different social strata in a population [1]. There is voluminous literature demonstrating a consistent stepwise relationship between socioeconomic status and the severity of oral conditions, suggesting oral health disparities are socially patterned [2,3]. However, oral health inequalities are predominantly supported by cross-sectional studies and evidence from cohort studies is increasing more recently [2].…”
Section: Introductionmentioning
confidence: 99%
“…From an analytical point of view, studies on intergenerational social mobility and adult oral health have typically adopted a conventional regression approach where four trajectories are formed (i.e., high‐high, high‐low, low‐high and low‐low by combining information on childhood and adulthood SEP) and compared in terms of their oral health in adult life 13–20 13–20 .…”
Section: Introductionmentioning
confidence: 99%
“…From an analytical point of view, studies on intergenerational social mobility and adult oral health have typically adopted a conventional regression approach where four trajectories are formed (i.e., high‐high, high‐low, low‐high and low‐low by combining information on childhood and adulthood SEP) and compared in terms of their oral health in adult life 13–20 13–20 . Such an approach is limited because it collapses ordered SEP groups into broad binary categories to form the trajectories, thus losing information as not all the mobility that occurs from childhood to adulthood is captured.…”
Section: Introductionmentioning
confidence: 99%